2000
DOI: 10.1111/j.1530-0277.2000.tb02028.x
|View full text |Cite
|
Sign up to set email alerts
|

The Genetics of Acute Functional Tolerance and Initial Sensitivity to Ethanol for an Ataxia Test in the LSxSS RI Strains

Abstract: Three conclusions can be drawn from this work: (1) Orbital sinus BEC at early time points (<5 min postinjection) may or may not accurately reflect brain EC in mice, dependent on genotype; (2) there is no genetic relationship between initial sensitivity and acute tolerance to stationary dowel ataxia in the LSXSS RIs; and (3) sex-specific factors affect low-dose ethanol responses on the stationary dowel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
3

Year Published

2001
2001
2011
2011

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 32 publications
0
17
3
Order By: Relevance
“…Likewise, too few measurements of the drug concentration also complicate this assessment especially when drug concentrations are rapidly changing Dietrich et al 2000;Gehle and Erwin 2000;Rustay et al 2001). Furthermore, venous blood measurements of the drug concentration often do not reflect the drug concentration in the brain (Wu et al 2001;.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, too few measurements of the drug concentration also complicate this assessment especially when drug concentrations are rapidly changing Dietrich et al 2000;Gehle and Erwin 2000;Rustay et al 2001). Furthermore, venous blood measurements of the drug concentration often do not reflect the drug concentration in the brain (Wu et al 2001;.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous investigators have recognized that measures of initial sensitivity often represent a mixture of sensitivity and acute tolerance development (SanMarina et al 1989;Khanna et al 1990;Khanna et al 1991;Ramsay and Woods 1997;Dietrich et al 2000;Gehle and Erwin 2000;Ponomarev and Crabbe 2002). Research investigating how initial drug sensitivity, acute tolerance and chronic tolerance are related is susceptible to finding spurious associations because a baseline value can influence the size of the drug effect (sensitivity) that in turn can influence the amount of acute and chronic tolerance that can develop.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are various behavioral tests of ethanol-induced ataxia. They include the stationary dowel, the Rotarod, the screen test, and the grid test involving measures of grip strength, balance, and coordinated movement Phillips et al, 1996;Browman and Crabbe, 2000;Deitrich et al, 2000;Gehle and Erwin, 2000). Although inbred strains of mice have been shown to differ on numerous measures of ethanol sensitivity, no one strain has been shown to be more or less sensitive across all tests of ethanol sensitivity (Crabbe, 1983;Crabbe et al, 1994).…”
Section: Tablementioning
confidence: 99%
“…Ethanol-induced ataxia is clinically important and a good measure of intoxication. Several studies using various measures of ataxia have shown differences in initial sensitivity and acute tolerance across inbred strains Browman and Crabbe, 2000;Deitrich et al, 2000;Gehle and Erwin, 2000;Kirstein and Tabakoff, 2001). The dowel test for ataxia is a fairly simple test of coordination and balance that allows for the measurement of both initial sensitivity and acute tolerance to ethanol.…”
mentioning
confidence: 99%